FAKE REALITY: WOMEN PORTRAYAL IN BEAUTY PRODUCT ADVERTISEMENTS OF PAKISTANI PRIVATE CHANNELS - Zarnab Rana (Jurnal Sosiologi Reflektif, 2021)
Since advertising was introduced many centuries ago, women have been objectified and, in some cases, insulted or belittled. The second wave of feminists challenged society's definition of femininity, and society's insistence on equating men with “thought” and women with “nature” and “body.” This paper aims to investigate the question of women portrayal in Pakistani media with “Jean Baudrillard theory of Simulacra and Simulation”. It focuses on how media and writing are constantly affected by hyperreality. Films, commercials, news, web-based media, and so on address fake real factors with the goal that the current world can't understand reality and innovation. Content analysis was used to emphasize how sexist media constructs an unattainable or objective image of female beauty. This paper shows how personal achievements and accomplishments are only acceptable if they meet the criteria of unrealistic beauty standards. The idea of being “perfect” is reinforced through media but mostly women are suffering with anxiety, depression and the feeling of being insecure in their homes. The fear of being inferior and rejection make them vulnerable and less competitive in society which develops a sense of passiveness and low self-esteem.Sejak dunia periklanan diperkenalkan, perempuan telah menjadi objek, dan dalam beberapa kasus mereka direndahkan dan mengalami penolakan. Gelombang feminis telah menentang definisi feminitas dan desakan masyarakat untuk menyamakan laki-laki dengan ‘pikiran’ dan perempuan dengan ‘nature’ dan ‘body’. Artikel ini bermaksud untuk menyelidiki bagaimana proses penggambaran perempuan di media Pakistan melalui teori Simulacra dan Simulasi Jean Baudrillard. Tulisan ini juga berfokus pada bagaimana media secara terus-menerus dipengaruhi oleh hiperrealitas. Film, iklan, berita, media berbasis website, dan yang lainnya membahas realitas palsu dengan tujuan agar dunia saat ini tidak memahami realitas dan inovasi. Analisis Konten digunakan untuk menekankan bagaimana media seksis membangun citra kecantikan perempuan. Hasil penelitian menunjukkan bagaimana pencapaian pribadi hanya dapat diterima jika telah memenuhi standar kecantikan yang tidak realistis. Gagasan untuk menjadi perempuan “sempurna” diperkuat melalui media, namun pada kenyataannya para perempuan justru mengalami kecemasan, depresi, dan perasaan tidak aman. Inferioritas dan dan ketakutan akan penolakan membuat mereka rentan dan kurang kompetitif dalam masyarakat, yang kemudian berkembang menjadi sikap pasif dan memiliki harga diri yang rendah.